SOSIALISASI PEMANFAATAN BETON SERAT HYBRID UNTUK PENINGKATAN DURABILITAS KONSTRUKSI BANGUNAN GEDUNG DI CV. SOKOGI REKSACIPTA - Deni, Delista Putri; Kurnianingsih, Oktavia; Majid, Aziz Abdul; Pratiwi, Kholis Hapsari; Nusantara, Johan Lautan Wijaya; Alfianarrochmah, Ilma; Saputra, Canggih Gilang Pradana Hardi; Legowo, Slamet Jauhari; Yanto, Fendi Hary (Jurnal Abdi Insani, 2025)
Building construction in the Soloraya area often encounters cracking problems. This problem is generally caused by various factors such as improper design, poor material quality, building age, etc. which can have an impact on durability and structural strength. Therefore, Appropriate Structure Research Group conducted a community service with the aim of providing solutions to be utilized in the construction of buildings in the Soloraya area. This service was carried out with CV. Sokogi Reksacipta which is a local construction consultancy service provider. The concrete innovation presented as a solution is hybrid fiber concrete that combines natural fibers, i.e. ramie fibers and synthetic microfibers with improved mechanical properties to increase resistance to cracking. Through a series of laboratory tests and data analysis, the effectiveness of using hybrid fiber concrete in reducing the risk of cracking and increasing the durability of concrete structures was evaluated. The method used in this community service is socialization of the use and method of making innovative concrete. From the results of this program, 93.75% of participants understood the socialization activities, therefore this program is expected to contribute to the development of more durable and sustainable concrete technology for building construction applications in the Soloraya area.